Analysis of Lead (Pb) and Cadmium (Cd) in Whitening Creams using Atomic Absorption Spectroscopy - A. T. Agustina; M. P. Primadi; H. Randhanugraha; K. Khotimah; I. Luriyani (Universitas Negeri Yogyakarta, 2021)
This research aims to determine the concentration of Lead (Pb) and Cadmium (Cd) metals contained in face whitening creams that are sold in store around Sleman, Yogyakarta. The analysis concentration of Pb and Cd levels in those whitening creams carried out using Atomic Absorption Spectrophotometer (AAS) at Chemistry laboratory of Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta. We used 5 different face whitening cream samples (here after indicated by sample A, B, C, D, E) that taken randomly with the range price of thousand rupiahs. The results of analysis showed that in the sample A contains of -0.729 ppm Pb and 1,199 ppm Cd; sample B covers 0,017 ppm Pb and 1,274 ppm Cd; in the sample C consists of 1,082 ppm Pb and 1,254 ppm Cd; in the sample D contains a total of 1.242 ppm Pb and 1.215 ppm Cd; and in the sample E consists of -0.409 Pb and 1.232 ppm Cd. The results of this research are useful as the bases of their heavy metal concentrations, thus the possibilities of counterfeiting of the products ingredients can be avoided. An effort should be made in order to tell the customers about the harmful effects of over consumption of the face whitening cream with heavy metal acumulations in the body.